Intrafamilial child homicide: an umbrella review of systematic reviews - Kim, Bitna (Journal of family violence, 2024)
Purpose: Systematic reviews on child homicide have proliferated recently, making it hard to keep up with their output. Using an umbrella review approach (i.e., a synthesis of systematic reviews), this study aimed to identify what aspects of child homicide have been examined in systematic reviews, synthesize systematic review findings, and discuss the implications for policy, practice, and future primary research. Method: The current study utilized an umbrella review approach to locate systematic reviews of studies on child homicide published in various disciplines. The final sample included fourteen systematic review articles published from 2010 to 2022. Results: The main research questions varied across systematic reviews, but they included risk factors, typology, statistics on incidence and prevalence, and punishment and disposition. Systematic reviewers highlighted the need for a database and monitoring system, multi-disciplinary Child Death Review Teams, parenting education, and women-friendly services and policies. Conclusions: More systematic reviews and meta-analyses need to be conducted, focusing on evidence-informed strategies, to inform child abuse policies and practices. It is also imperative that the child homicide research community establish knowledge dissemination strategies to build large-scale datasets and translate research results into effective risk management practices.